Geography of experience: space-time and body-consciousness: Geography of experience: space-time and body-consciousness (Élisée - Revista de Geografia da UEG, 2023)
Through experience, one moves towards its phenomenology in geographical existence. Disart, existence, founded by Space and Time, opens its experience in manifestations by spatial (body) and temporal (consciousness), giving them character a posteriori, phenomenal. From this, from the natural world, by the being-in-the-world, it circulates with the mental world, through the world-in-the-being: from perception to understanding. This is the geographical existence, by being-in (spatial) and being-with (social), in the social space. Moreover, in the relationships of the bodies (for-itself) and consciences (in-itself), space-time is conceived in the moments that open events through actions, promoted by intentionalities, marking events. Thus, mental geography was perscrutod, through the ex (outside) peri (around) entia (knowledge). To this end, the disease was conceived as an I-Being, from the geographical Self (in the desires to displace and belong) to the Being, Body-Consciousness. It also opens the peri as peri corporal in the environment (situations) and the peri surrounding the environment (relationships). Furthermore, towards the direction of the ex, we were asked about the physical (concrete) movement, the imagined (abstract) and, also, to the unknown by propelling the world known to the desired world. Depending on the geographical-existential, it deepened, in a synthetic-analytical way, in the geographical experience.
Keywords: Geographic thinking; Existencial geography; Mental geography; experience